Bathhouse - Pablo, Crisaldo; Raganit, Rowena; Alcantara, Jet.; Ranay, Andoy; Pumaloy, Rey. ([S.l.] ProGay Philippines, 2006)
Bathhouse seeks to expose the cruel world that gays have waved within the dark stingy walls of quasi-bathhouses in the Philippines. The story revolves around the lives of men who frequent the seedy bathhouse 'Klub Hombre' where you have to be masculine, attractive, huge in order to e accepted to the exclusive club.
DVD
Written and directed by Crisaldo Pablo, cinematography Rowena Raganit.
Jet Alcantara, Andoy Ranay, Rey Pumaloy.
Keywords: Gays--Drama.; Feature films